(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The values of density & viscosity for the binary liquid mixtures of N, N dimethylaniline & N, N diethylaniline alkanols (methanol & ethanol) have been measured over entire range of composition at T = 298k to 313k. Using these excess molar volumes (VE) & deviations in viscosity have been correlated with Redlich - Kister type polynomial equation to derive the binary coefficients & standard deviation.